DSSC Heterojunction photoelectrode based ZnO-nanorod/TiO2; Dependency of photoelectrode morphology investigated by calculating I-V curves - ANNISA APRILIA; HERI FERNANDO; LUSI SAFRIANI; AYI BAHTIAR; RAHMAT HIDAYAT (Jurnal Material dan Energi Indonesia, 2020)
The simple diode model equation can be used to derive solar cell parameters based on current density-voltage curve. This calculation has an objective to study the working of ZnO nanorod/TiO2 as photoelectrode in dye-sensitized solar cell (DSC). As a function to collect and transport the electron inside the cell, ZnO-Nr/TiO2 bilayer heterojunction works as photoanode. The equivalent circuit in real solar cell is usually based on two diode model by considering presence a large of recombination process inside the cell (non-ideal diode). We simplified the equivalent circuit with only one diode and one resistor (Rsh) in parallel with a series resistor (Rs) related to photovoltage occurs. The current loss due to back reaction and recombination process which is appeared at interfacing area between photoanode/dye and electrolyte corresponds as parallel resistance (Rp). An ideality factor (m) due to non-linear b-recombination process which is occurred inside the cell is also derived using this model. The comparison between commonly photoanode (single type of TiO2 mesoporous), multilayer ZnO nanorod/TiO2, and planar heterojunction ZnO/TiO2 is also observed in order to emphasize the interface quality of photonode to the such solar cell parameters